Populáris irodalom és háborús erőfeszítés: Gustave Le Rouge esete - Kálai, Sándor (Studia Litteraria, 2015)
Analysing representations of war, we tend to consult “canonized” texts, forgetting that authors of popular literature can also add important aspects to the topic. Thisessay explores this slice of literature through one particular case. In 1917 and 1918, Gustave Le Rouge, one of the most original and productive authors of French popular literature, published five short stories in a series called Patrie (Homeland) by Rouff publisher. In the first part of the essay, I discuss the portrayal of the characters and the representations of war in the texts, while the second part focuses on the various levels of narration and literary communication, especially on the vehicle and the forms of blended written and visual codes.